Impact of Habit on Online Fraud Mitigation - Kurniawan, Kevin; Soeherman, Bonnie (Jurnal Riset Akuntansi dan Keuangan, 2021)
User habits and their use of online mediums can make a bit difference, since the cyberspace is full of opportunities, as well as risks. Carelessness, especially in terms of data storage, information, and financial practices can lead to irreparable damages. The present paper provides a comprehensive overview of how the digital space has changed and how criminals take advantage of the vulnerabilities of internet users. The first section outlines the risk behavior and habits of users that invite cybercriminals and increase the threat of intrusion and data leak. The next section is dedicated to the detailed analysis of habits that can help users in prevent the crimes and mitigate their consequences. A set of recommendations is also presented towards the end of the paper, which is intended to assist users in identifying dubious online activities and prevent them before the crime happens. The paper makes use of scholarly and journal articles to establish its arguments